Evaluating Mechanical Properties of Macro-Synthetic Fiber-Reinforced Concrete with Various Types and Contents - Daneshfar, M.; Hassani, A.; Aliha, M.R.M.; Berto, F. (Проблемы прочности, 2017)
Concrete, as one of the most widely used construction materials, has a brittle behavior. Adding fibers with different types and contents would affect the ductility behavior and mechanical properties of concrete. Hence, an experimental study was conducted to investigate effects of type and content of polymer fibers on mechanical properties of fiber-reinforced concrete such as flexural strength, compressive strength, indirect tensile strength, and elastic modulus. In the present research, the concrete samples were made and, then, evaluated, using three different types of polymer fibers, including twisted, barchip, and fibrillated, with the contents of 0.2, 0.4, and 0.6 volume percentages, respectively. The results showed that by adding fibers to the concrete samples, the flexural and tensile strength was increased by 19.6–81.69% and 0.84–34.29%, respectively; besides, the addition of the fibers to concrete reduced the compressive strength and elasticity modulus by 4.57–26.32% and 12.48–37.08%, respectively. The concrete containing twisted and barchip fibers, despite the different types of fibers, had similar flexural performance.